Highly Stable and End‐group Tuneable Metal–Organic Framework/Polymer Composite for Superior Triboelectric Nanogenerator Application. Issue 34 (6th October 2022) - More, Yogeshwar D.; Saurabh, Satyam; Mollick, Samraj; Singh, Sachin Kumar; Dutta, Subhajit; Fajal, Sahel; Prathamshetti, Anil; Shirolkar, Mandar M.; Panchal, Suresh; Wable, Minal; Ogale, Satishchandra; Ghosh, Sujit K.
Abstract: Triboelectric nanogenerators (TENGs) are receiving significant attention lately as efficient mechanical energy harvesting devices. They are finding multiple uses in numerous low‐power applications. Current TENG designs, although innovative, fall short on practical demands like performance tunability, modulatory, and stability. This invites further research in the use of new materials for TENGs. Metal‐organic frameworks (MOFs) offer a unique feature of molecular tunability to optimize energy conversion which has been exploited in this study. Prototypal hybridization strategy is deployed on underexplored isoreticular subfamily UiO‐66(Zr) MOFs through UiO‐66‐X/PVDF (X = H or Br) composites for TENG output tuning and amplification. UiO‐66‐X/PVDF exhibits good aquatic and thermal stability accompanying substantial boost in TENG power. Functionalized H2 BDC linker improved surface roughness and potential. UiO‐66‐Br encased in PVDF matrix boosted charge and TENG performance by enhancing electrification. Computational details support observations. Device captures waste energy in a vertical contact‐separation mode and functions consistently amidst diverse environmental settings. Functionalized TENG‐2 delivers a Vp–p of 110.41 V, which is 2.92 times and 14.12 times higher than unfunctionalized TENG‐1 and PVDF film, respectively. Findings reveal maiden example of ligand‐mediated functional group‐driven performance tuning of TENG and mechanistic insight using isoreticular MOFs/PVDF composites. Abstract : For the first time, we present a functional group‐driven tuning of organic ligand chemistry (and hence metal‐organic frameworks, MOFs) that has a direct impact on triboelectric nanogenerator (TENG) output performance. Isoreticular frameworks of the UiO‐66 family (compounds 1 and 2) are strategically used keeping nearly identical dimensional and operating conditions of composite‐fabricated devices (1/PVDF and 2/PVDF), providing a rational platform for elucidating, deploying, and exploiting functional groups electronic effects to govern TENG output performance. The fabricated device was found to give consistent and steady TENG output with exceptional durability and reproducibility features.